Faktor-Faktor yang Memengaruhi Kinerja Pegawai Pusdiklat Anggaran dan Perbendaharaan Setelah Reformasi Birokrasi Diterapkan - Irwan Hermawan; M. Parulian Hutagaol; Joko Affandi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
This study examined the influence of bureaucratic reform policies that have been implemented at Training and Education Center of Budget and Treasury, Ministry of Finance since 2007 on employee performance. Bureaucratic reform in its implementation using the concept of two-way social approach, ie persuasive and coercive. Persuasive approach to drive performance through improved remuneration. While the approach of coercion restriction or supervision, and strict punishment to avoid attitudes and behaviors that can be detrimental to the organization through the dimensional change of mindset, structuring the organization and business process, and discipline improvement and human resource management. This study used a quantitative approach with a survey method. The results showed that the bureaucratic reform give an effect and improve the employee performance. Base on the result, it is recommended that bureaucratic reform policy can be implemented to other ministries and institutions to improve the employee performance.